DESIGN OF CPW FED TWO LAYERED RECTANGULAR DIELECTRIC RESONATOR ANTENNA FOR 5G MOBILE COMMUNICATIONS - AHMED, EMAD S. (Journal of Duhok University, 2021)
In this research, a dielectric resonator antenna (DRA) is designed to operate in the frequency bands of fifth-generation mobile communications. The antenna consists of two rectangular dielectric resonators arranged in two layers. Each DR has its own height and relative dielectric constant. The relative dielectric constant of the lower and the upper resonators are 9.8 and 10.8 respectively. The DRA is fed by a 50 ohm coplanar waveguide (CPW) type feeder. The dielectric resonators and the CPW system are placed on FR-4 substrate with dielectric constant of 4.7 and 1.5 mm thickness. The operating frequency covers the band from (24-31) GHz with voltage standing wave ratio (VSWR) equal or less than two. The antenna shows good radiation performance with linear maximum gain of about (5-7) dBi over the designated frequency band. The antenna is categorized as miniaturized and low profile antenna.